Using DayCENT to Simulate Carbon Dynamics in Conventional and No‐Till Agriculture. Issue 3 (30th April 2013) - Chang, Kuo-Hsien; Warland, Jon; Voroney, Paul; Bartlett, Paul; Wagner-Riddle, Claudia
Abstract : The DayCENT model was employed to simulate the effects of conventional tillage (CT) and no‐till (NT) practices on the dynamics of soil organic carbon (SOC) over 9 yr in a rotational cropping system in Southern Ontario, Canada. Observations of site properties and eddy covariance measurements were used to assess crop productivity, net ecosystem productivity (NEP), and SOC changes. The validated model captured the dynamics of grain yield and net primary production, which indicated that DayCENT can be used to simulate crop productivity for evaluating the effects of tillage on crop residues and heterotrophic respiration ( R h ) dynamics. The simulation suggested that CT enhanced the annual R h relative to NT by 38.4, 93.7 and 64.2 g C m −2 yr −1 for corn ( Zea mays L.), soybean [ Glycine max (L.) Merr], and winter wheat ( Triticum aestivum L. ), respectively. The combined effect of incorporating crop residues and increased cultivation factors enhanced R h in CT by 35% relative to NT after disk cultivation in the spring. The simulated NEP varied with crop species, tillage practices, and timing/length of the growing season. The seasonal variation of the total SOC pool was greater in CT than NT because of tillage effects on C transfer from the active surface SOC pool to the active soil SOC pool at a rate of 50 to 100 g C m −2 yr −1 . The NT method practiced during the study period accounted for a 10.7 g C m −2 yr −1 increase in the slow SOC pool. The validated DayCENT model may be applied for longer‐term simulations in similar ecosystems for a variety of climate change experiment.